Derepression of Y-linked multicopy protamine-like genes interferes with sperm nuclear compaction in D. melanogaster. - Park, J.I.; Bell, G.W.; Yamashita, Y.M. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Across species, sperm maturation involves the dramatic reconfiguration of chromatin into highly compact nuclei that enhance hydrodynamic ability and ensure paternal genomic integrity. This process is mediated by the replacement of histones by sperm nuclear basic proteins, also referred to as protamines. In humans, a carefully balanced dosage between two known protamine genes is required for optimal fertility. However, it remains unknown how their proper balance is regulated and how defects in balance may lead to compromised fertility. Here, we show that a nucleolar protein, modulo, a homolog of nucleolin, mediates the histone-to-protamine transition during Drosophila spermatogenesis. We find that modulo mutants display nuclear compaction defects during late spermatogenesis due to decreased expression of autosomal protamine genes (including Mst77F) and derepression of Y-linked multicopy Mst77F homologs (Mst77Y), leading to the mutant's known sterility. Overexpression of Mst77Y in a wild-type background is sufficient to cause nuclear compaction defects, similar to modulo mutant, indicating that Mst77Y is a dominant-negative variant interfering with the process of histone-to-protamine transition. Interestingly, ectopic overexpression of Mst77Y caused decompaction of X-bearing spermatids nuclei more frequently than Y-bearing spermatid nuclei, although this did not greatly affect the sex ratio of offspring. We further show that modulo regulates these protamine genes at the step of transcript polyadenylation. We conclude that the regulation of protamines mediated by modulo, ensuring the expression of functional ones while repressing dominant-negative ones, is critical for male fertility.